Pengaruh Anime dan Budaya Jepang dalam Gaya Hidup Mahasiswa di Banda Aceh: The Influence of Anime and Japanese Culture on the Lifestyle of University Students in Banda Aceh - Raudha, Silvia; Azwarfajri, Azwarfajri; Musdawati, Musdawati (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2024)
The emergence of anime among university students has influenced the formation of a distinctive lifestyle, primarily through the imitation of concepts depicted in these anime. Consequently, this paper examines the impact of anime on the lives of university students in Banda Aceh, aiming to understand both the positive and negative effects of anime and Japanese culture on students' lifestyle changes. This qualitative research utilized observation, interviews, and documentation as data collection methods. The findings reveal various forms of lifestyle changes, including alterations in motivation, social interaction, the incorporation of the Japanese language into daily life, the adoption of anime fashion, imitative behaviors, and shifts in students' perspectives towards anime and Japanese culture. The positive impacts identified from anime include the development of Japanese language skills, anime serving as a source of inspiration, and anime facilitating social interaction among students. However, the study also highlights negative impacts, such as the excessive amount of time spent watching anime, experiences of hallucinations, and exposure to inappropriate content or content overly focused on sexuality. Abstrak Munculnya anime di kalangan mahasiswa memberikan pengaruh dalam membentuk gaya hidup tersendiri akibat mengimitasi konsep anime tersebut. Oleh karena itu tulisan ini mengkaji bagaimana dampak anime bagi kehidupan mahasiswa di Banda Aceh untuk mengetahui dampak positif dan negatif dari pengaruh anime dan budaya Jepang terhadap perubahan gaya hidup mahasiswa. Penelitian kualitatif ini menggunakan teknik pengumpulan data observasi, wawancara dan dokumentasi. Hasil penelitian menunjukkan terdapat beberapa bentuk perubahan gaya hidup yaitu perubahan motivasi, interaksi sosial, penggunaan bahasa Jepang dalam kehidupan sehari-hari, adopsi fashion anime, serta perilaku imitasi, hingga perubahan perspektif mahasiswa terhadap anime dan budaya Jepang. Adapun dampak positif yang ditimbulkan anime kepada mahasiswa adalah pengembangan keterampilan berbahasa Jepang, anime sebagai sumber inspiratif dan anime sebagai pembangun interaksi sosial bagi mahasiswa. Namun, anime juga memberikan dampak negatif yaitu menghabiskan banyak waktu untuk menonton, halusinasi, serta konten yang tidak sesuai atau lebih mengarah ke seksualitas.